About Ambekova Bovush’s song legacy - B. Kh. Borlykova (Nomadic Civilization: Historical Research, 2025)
This article is devoted to the study of the folklore heritage of Bovush Purveevna Ambekova. Much of this legacy was published in 2006 in the book “Ceczn bulg” (“The Spring of Wisdom”). However, some of the materials still remain unpublished (tape recordings from the 1970s and 1980s and self-recordings of the storyteller). The author of the article used a descriptive research method. She reviewed the manuscripts in 2014, and also previously transcribed her audio recordings of songs. Unfortunately, Bogush Ambekova’s legacy has not yet been scientifically investigated. In this connection, this topic was taken by the author of this article. At the end of the article, the author came to the conclusion that Bogush Ambekova left an invaluable folklore legacy. No matter how many years have passed, her legacy will be preserved and will be heard by the people.